2020
DOI: 10.1007/s40864-020-00128-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Dwell Time on the Reliability of Urban Light Rail Operations

Abstract: The present study investigates the determinants of vehicle dwell time at stations in urban light rail networks. Using data collected from an on-board automatic passenger counting system of the tramway network of the French city of Nantes over a long period, the study performs graphical and statistical analyses enabling the identification of cause-and-effect relationships of a number of attributes on the dwell time and its reliability. The results confirm the significance of the boarding and alighting passenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Most of the literature looks at station exchange time for buses, or for the BRT in China (Li et al, 2012), which is similar to the rail system except that passengers rarely board and alight through the same door. Christoforou et al (2016) reviewed the state-of-the-art of existing studies and statistical models for urban rail. In particular, there are many models, from the simplest TCQSM ( 2003), which only considers boarding and alighting at the most critical door, to the most sophisticated -Weston's model verified by Harris and Anderson (2007) on the London and Hong Kong rail networks.…”
Section: State Of the Artmentioning
confidence: 99%
“…Most of the literature looks at station exchange time for buses, or for the BRT in China (Li et al, 2012), which is similar to the rail system except that passengers rarely board and alight through the same door. Christoforou et al (2016) reviewed the state-of-the-art of existing studies and statistical models for urban rail. In particular, there are many models, from the simplest TCQSM ( 2003), which only considers boarding and alighting at the most critical door, to the most sophisticated -Weston's model verified by Harris and Anderson (2007) on the London and Hong Kong rail networks.…”
Section: State Of the Artmentioning
confidence: 99%
“…Surveys have been conducted by Currie et al [26], in which the congestion was found to be influenced by the number of passengers on board (congestion inside the vehicle). Christoforou et al [27] studied this congestion using data collected from an automatic passenger counting system on board urban light rail systems. The authors state that the volumes of boarding passengers, alighting passengers, and passengers on board affect the LOS, as well as vehicle design (e.g., low floor), time of day, and station location.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, URT systems can promote the development of a city and even reshape urban structure such as by enhancing or mitigating work–residence separation. The topological network of URT systems and their coverage can be seen as the transportation infrastructure supply from an urban planner’s point of view, with the network traffic flow of URT systems representing the demand side [ 7 , 8 , 9 ]. Increasing traffic demand drives the extension of the URT system, with the new rail lines generating still further demand.…”
Section: Introductionmentioning
confidence: 99%